As recentes falhas no gerenciamento de barragens de rejeito em Minas Gerais - Guilherme Eduardo Macedo Cota; Antônio Pereira Magalhães Junior – (Confins)
The recent events of failure in the management of tailing dams in Minas Gerais have raised several questions about the gaps in the legal apparatus and in the management system of the structures that allowed such events to occur. Therefore, the present work aims to investigate, from a bibliographical review, the causes that led to the failure events which occurred in dam B1 in Itabirito in 2014, in Fundão dam in Mariana in 2015 and in dam I in Brumadinho in 2019. The obtained results indicate that the causes of these ruptures are related to gaps in the structure licensing process, as well as non-compliance with the dam operations manual. Furthermore, the process of self-monitoring of dams in Minas Gerais has proven to be flawed, mainly because the three dams adopted as a case study were declared stable and even so they have broken.